A Case Study on the Effects of Foam and Seat Pan Inclination on the Deformation of Seated Buttocks Using MRI. Issue 1 (2nd January 2021) - Wang, Xuguang; Savonnet, Léo; Capbern, Loïc; Duprey, Sonia
OCCUPATIONAL APPLICATIONS: We investigated the effects of seat pan inclination and foam on the deformation of the seated buttocks using an upright MRI system. From observations among four healthy males, we found that soft tissue deformation under the ischial tuberosity (IT) could be reduced not only by using a soft cushion, but also by decreasing the shear force on the seat pan surface. These results suggest that soft tissue deformation could be used as an objective measure for assessing seating discomfort and injury risk, by accounting for the effects of both contact pressure and shear. We also confirmed that the gluteus maximus (GM) muscle displaced away from the IT once seated. As peak pressure and shear are most likely located below the IT, more realistic computational human body models in this region are needed that consider muscle sliding. TECHNICAL ABSTRACT: Background: A full understanding of soft tissue deformations, particularly in the gluteal region in a seated position, would be helpful for improving seat comfort and reducing the injury risk of seated people. Thanks to recent developments in medical imaging, direct observations of soft-tissue deformations under realistic loading conditions is now possible using open MRI. Purpose: The purpose of this work was to investigate the effects of seat pan inclination and foam on the deformation of soft tissues in the gluteal region using an open MRI. Methods: Four healthy male participants completed the experiment, in which a positional MRI scanner was used to scan the buttocks and part of the thighs. Three seating conditions were tested by varying the seat pan angle (A_SP) and cushion material while the backrest was fixed at 22 degrees from the vertical: 1) A_SP = 7° without foam (Reference); 2) A_SP = 0° without foam (Shear); 3) A_SP = 7° with a 50 mm thick foam on the seat pan (Foam). In addition, one configuration (Unloaded), with the buttocks being unsupported, was also scanned for comparison. After segmenting images, we calculated the volumes of the gluteus maximus (GM) muscle and subcutaneous fat in three regions of interest under the ischial tuberosity (IT) for each condition. Results: Once seated, the GM displaced away from the IT laterally and posteriorly. For all participants, the largest tissue deformation was observed in the Shear condition, while the smallest was found in the Foam condition. Conclusions: The present study provides quantitative data needed for validating buttock-thigh finite element models. Future work is needed to link soft tissue deformation with discomfort perception.